2020
DOI: 10.1016/j.molcel.2020.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of MLX-Family Transcription Factors to Lipid Droplets Regulates Metabolic Gene Expression

Abstract: Highlights d Global RNAi screening identifies determinants of lipid storage in human macrophages d RNAi screen hits belong to six major classes with distinct lipid droplet morphology d MLX family of transcription factors bind to lipid droplets via amphipathic helices d Lipid droplet binding reduces MLX/MLXIP/MLXIPL transcriptional activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(135 citation statements)
references
References 109 publications
(129 reference statements)
4
131
0
Order By: Relevance
“…Indeed, these findings are consistent with glucose-mediated activation of MLX family of transcription factors (Kawaguchi et al, 2001;Ma et al, 2005), including ChREBP, and target genes that promote de novo lipogenesis in BAT (Mottillo et al, 2014;Sanchez-Gurmaches et al, 2018;Trayhurn, 1979;Yu et al, 2002). This finding is also consistent with our recent report of increased expression of ChREBP/MLX-target genes in cells lacking LDs through DGAT inhbition (Mejhert et al, 2020). Moreover, they agree with previous studies that suggest a feedback mechanism correlating reduced DGAT activity with inhibiton of the SREBP1mediated lipogenic pathway (Chitraju et al, 2017;Choi et al, 2007;Monetti et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, these findings are consistent with glucose-mediated activation of MLX family of transcription factors (Kawaguchi et al, 2001;Ma et al, 2005), including ChREBP, and target genes that promote de novo lipogenesis in BAT (Mottillo et al, 2014;Sanchez-Gurmaches et al, 2018;Trayhurn, 1979;Yu et al, 2002). This finding is also consistent with our recent report of increased expression of ChREBP/MLX-target genes in cells lacking LDs through DGAT inhbition (Mejhert et al, 2020). Moreover, they agree with previous studies that suggest a feedback mechanism correlating reduced DGAT activity with inhibiton of the SREBP1mediated lipogenic pathway (Chitraju et al, 2017;Choi et al, 2007;Monetti et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…We conclude that PISD-LD-GFP localizes in part to lipid droplets. Importantly, recent proteomics-based inventories of LD proteins in multiple cell types (U2OS, THP-1, SUM159) identified native PISD in purified lipid droplet fractions (Bersuker et al, 2018;Mejhert et al, 2020).…”
Section: An Alternatively Spliced Variant Of Pisd Localizes To the LImentioning
confidence: 99%
“…Several types of structural features of LD proteins have been identified that confer LD targeting (Kory et al, 2016). Some amphipathic alpha helices confer reversible targeting to the LD surface from the cytosol/aqueous phase, and a second type of LD targeting determinant consists of a hydrophobic segment that forms a lipid-embedded hairpin (Mejhert et al, 2020).…”
Section: Pisd-ld Possesses Overlapping Ld and Mitochondrion Targetingmentioning
confidence: 99%
“…It is now well-established that LDs can transiently accumulate proteins from other cellular compartments (Welte, 2007). This has been particularly documented for a number of proteins involved in nuclei acid binding/transcriptional regulation: For example, in mammalian cells, MLX and Perilipin 5 can either be present on LDs or move into the nucleus to regulate transcription (Gallardo-Montejano et al, 2016;Mejhert et al, 2020). In bacteria, the transcriptional regulator MLDSR (microorganism lipid droplet small regulator) is sequestered to LDs under stress conditions (Zhang et al, 2017).…”
Section: Broader Insights Into Protein Sequestrationmentioning
confidence: 99%
“…Sequestration of the ER protein Sturkopf to LDs has been proposed to mitigate its repressive effects on an ER-associated enzyme (Werthebach et al, 2019). And a number of proteins involved in transcriptional regulation can be sequestered on LDs in bacteria, fungi, and mammalian cells (Aramburu et al, 2006;Gallardo-Montejano et al, 2016;Mejhert et al, 2020;Romanauska & Kohler, 2018;Zhang et al, 2017). However, in only a few cases is the function of protein sequestration on LDs understood at a molecular level.…”
Section: Introductionmentioning
confidence: 99%